If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -2(2x + 2) = 6 Reorder the terms: 2x + -2(2 + 2x) = 6 2x + (2 * -2 + 2x * -2) = 6 2x + (-4 + -4x) = 6 Reorder the terms: -4 + 2x + -4x = 6 Combine like terms: 2x + -4x = -2x -4 + -2x = 6 Solving -4 + -2x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -2x = 6 + 4 Combine like terms: -4 + 4 = 0 0 + -2x = 6 + 4 -2x = 6 + 4 Combine like terms: 6 + 4 = 10 -2x = 10 Divide each side by '-2'. x = -5 Simplifying x = -5
| 41-1/3b=37 | | x^8+x^7+x^6=0 | | 5*3/4-1 | | 900+900+3x=700+500+9x | | 1/2I+9=14 | | 3x-3(4x-17)=96 | | 8y/12=6/9 | | 5x-11=35 | | 3*(3/4)^2-2*3/4 | | 4(c+6)=1/2(-2c-20) | | -4x+3(3x-17)=-76 | | 4b-4-11b-6= | | c-2/2+12=36 | | 0=0.001(0.732x^2+15.417x+605.738) | | 900+900+3x=700+500+9z | | x+1=7x | | 5x+12=4x+8 | | 49-49+81= | | 5x-2(6x+12)=53 | | 6x-3(6x-10)=162 | | x+10/2=42 | | 2x-2(2x-3)=-6 | | 2(x+4)=5xw+1 | | -3+-3+-2+-2+-2+-2+-1+-1+0+0+1+1+3+4= | | 4=(2+x)/2 | | 10j-10=3j-5 | | 7(x-3)=-4 | | -1=(8+x)/2 | | -4y+8=-2(4y+8) | | 7x+-1=4x+3 | | 0.4x+0.2(30)=0.3(x+30) | | -5x-7(-3x+9)=113 |